2014
DOI: 10.1371/journal.pone.0104157
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Profiling of Human Myocardial Tissues Distinguishes Ischemic from Non-Ischemic End Stage Heart Failure

Abstract: The molecular differences between ischemic (IF) and non-ischemic (NIF) heart failure are poorly defined. A better understanding of the molecular differences between these two heart failure etiologies may lead to the development of more effective heart failure therapeutics. In this study extensive proteomic and phosphoproteomic profiles of myocardial tissue from patients diagnosed with IF or NIF were assembled and compared.Proteins extracted from left ventricular sections were proteolyzed and phosphopeptides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…We have observed that levels of OPN-a were inversely related to myocardial fibrosis in the presence of similar decay of systolic function. We have detected larger myocardial deposits of type I collagen, fibronectin and fibroblasts in ICM rather than DCM hearts [31], in accord with previous studies [34][35][36][37][38]. Our data are also consistent with proteomic analysis performed by us on the same LV samples [31], which show the up-regulation of pro-apoptotic and pro-fibrotic factors in ICM failing hearts with overt fibrosis (ICM).…”
Section: Discussionsupporting
confidence: 92%
“…We have observed that levels of OPN-a were inversely related to myocardial fibrosis in the presence of similar decay of systolic function. We have detected larger myocardial deposits of type I collagen, fibronectin and fibroblasts in ICM rather than DCM hearts [31], in accord with previous studies [34][35][36][37][38]. Our data are also consistent with proteomic analysis performed by us on the same LV samples [31], which show the up-regulation of pro-apoptotic and pro-fibrotic factors in ICM failing hearts with overt fibrosis (ICM).…”
Section: Discussionsupporting
confidence: 92%
“…Experiments with a TREK-1 mutant, which lacks the PKA-dependent phosphorylation site, or pharmacological studies using PKA inhibitors will be informative in this context (32). Interestingly, POPDC1 is also subject to β-adrenergic-dependent phosphorylation (33,34). Thus, the regulation of POPDC1 involving cAMP binding, subcellular localization, and phosphorylation of itself and of interacting proteins deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins bound to the beads were pre-digested with 0.2% of RapiGest SF (Waters Corporation, Milford, MA, United States) in 50 mM ammonium bicarbonate (Schechter et al, 2014). After pre-digestion, samples were reduced with 10 mM Tris (2-carboxyethyl) phosphine hydrochloride (TCEP-HCl) and alkylated with 25 mM iodoacetamide, followed by overnight digestion at 37 • C with sequencing grade trypsin (Promega, Madison, WI, United States) in 1:50 trypsin/protein ratio.…”
Section: On-bead Trypsin Digestionmentioning
confidence: 99%